2001
DOI: 10.1002/1099-0682(200103)2001:3<651::aid-ejic651>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Redox-Active Conjugated Palladium Homobimetallic Complex

Abstract: The π‐conjugated molecule N,N′‐bis(4′‐dimethylaminophenyl)‐1,4‐benzoquinone diimine (L2) was incorporated into the palladium(II) complex 1 bearing the N,N′‐bis(2‐phenylethyl)‐2,6‐pyridinedicarboxamide ligand, to afford the redox‐active conjugated palladium(II) homobimetallic complex 2. An X‐ray crystal structure determination of 2 reveals that two palladium complex units are bridged by the quinone diimine moiety to form the C2‐symmetrical 2:1 complex with an anti configuration, and that the bridging π‐conjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 44 publications
2
17
0
Order By: Relevance
“…Treatment of L with [PdCl 2 (MeCN) 2 ] in acetonitrile led to the formation of the conjugated polymeric complex 2 , in which palladium centers are incorporated in the main chain (Scheme ). The electronic spectrum of 2 in DMSO exhibited a strong, broad absorption around 600–1000 nm, probably assignable to a low‐energy charge‐transfer transition with significant contribution from palladium; this indicates the coordination of the quinonediimine nitrogen atoms to palladium centers 5. The broad absorption band supports the formation of the conjugated polymeric complex 2 6.…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…Treatment of L with [PdCl 2 (MeCN) 2 ] in acetonitrile led to the formation of the conjugated polymeric complex 2 , in which palladium centers are incorporated in the main chain (Scheme ). The electronic spectrum of 2 in DMSO exhibited a strong, broad absorption around 600–1000 nm, probably assignable to a low‐energy charge‐transfer transition with significant contribution from palladium; this indicates the coordination of the quinonediimine nitrogen atoms to palladium centers 5. The broad absorption band supports the formation of the conjugated polymeric complex 2 6.…”
Section: Methodsmentioning
confidence: 86%
“…Transition metal directed assembly is regarded as a useful approach to an architecturally controlled formation of conjugated polymeric or macrocyclic complexes with π‐conjugated ligands 4. We have already demonstrated that the redox‐active π‐conjugated ligand N , N ′‐bis(4‐dimethylaminophenyl)‐1,4‐benzoquinonediimine (L) serves as a bridging ligand to afford the conjugated homobimetallic palladium( II ) complex [L′PdLPdL′] ( 1 ) with the palladium( II ) complex bearing the N‐heterocyclic tridentate podand ligand N , N ′‐bis(2‐phenylethyl)‐2,6‐pyridinedicarboxamide (L′) 5. Complex 1 is present as a mixture of syn and anti isomers in dichloromethane.…”
Section: Methodsmentioning
confidence: 99%
“…Ϫ 1 H NMR (400 MHz, CD 3 CN): δ ϭ 3.17 (t, J ϭ 6.9 Hz, 4 H), 3.76 (q, J ϭ 6.9 Hz, 4 H), 7.15 (dd, J ϭ 8. 5,1.0 Hz,2 H),7.21 (ddd,J ϭ 7.7,4.9,1.0 Hz,2 H),7.32 (ddd,J ϭ 7.7,1.0,0.8 Hz,2 H),7.45 (dd,J ϭ 7.5,1.0 Hz,2 H),7.55 (dd,J ϭ 8.5,7.5 Hz,2 H),7.69 (td,J ϭ 7.7,1.9 Hz,2 H),8.54 (ddd,J ϭ 4.9,1.9,0.8 Hz,2 H),9.70 (br,2 H H 5.51, N 12.25; found C 73.29, H 5.33, N 12.15.…”
Section: Synthesis Of 15-bis[2-(2-pyridyl)ethylamino]-910-anthraquimentioning
confidence: 99%
“…[3] However, the p-quinone complexes, in which a quinone oxygen coordinates to a high valent transition metal, have not been investigated extensively, [4] despite the elucidation of their coordination and redox properties in catalysis. In our previous papers, [5] the π-conjugated molecule, N,NЈ-bis(4Ј-dimethylaminophenyl)-1,4-benzoquinone diimine, was introduced to the palladium(II) complex bearing the N-heterocyclic tridentate podand ligand, affording a redoxactive π-conjugated palladium(II) homobimetallic complex, in which the redox properties of the quinone diimine moiety are modulated by complexation. These results prompted us to investigate the redox properties of the transition metal complexes with p-quinones and to characterize the complexes structurally.…”
Section: Introductionmentioning
confidence: 99%
“…[8] The square-planar [2]rotaxane ligand design consists of a tridentate benzylic amide macrocycle and a monodentate thread (Figure 1 d). The macrocycle incorporates a 2,6dicarboxyamidopyridine unit to exploit the palladium chemistry recently developed [9] by Hirao and co-workers. The thread contains a pyridine donor group substituted with appropriately bulky stoppers in either the 2,6-or 3,5-positions.…”
mentioning
confidence: 99%